DEVELOPMENT MODEL OF MEDICAL TOURISM VILLAGE CONCEPT TRI HITA KARANA IN LEMUKIH VILLAGE, SAWAN SUB-DISTRICT, BULELENG REGENCY - Yudi Aryawan, kadek (Universitas Aisyah Pringsewu, 2024)
This research plays a crucial role in supporting the direction of policies and programs of the Bali Provincial Government, known as